2018
DOI: 10.3168/jds.2017-13731
|View full text |Cite
|
Sign up to set email alerts
|

α-Lactalbumin-oleic acid complex kills tumor cells by inducing excess energy metabolism but inhibiting mRNA expression of the related enzymes

Abstract: Previous studies have demonstrated that the anti-tumor α-lactalbumin-oleic acid complex (α-LA-OA) may target the glycolysis of tumor cells. However, few data are available regarding the effects of α-LA-OA on energy metabolism. In this study, we measured glycolysis and mitochondrial functions in HeLa cells in response to α-LA-OA using the XF flux analyzer (Seahorse Bioscience, North Billerica, MA). The gene expression of enzymes involved in glycolysis, tricarboxylic acid cycle, electron transfer chain, and ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…The other proteins included enzymes in the mitochondria that are mainly related to catabolism. Specifically, aconitate hydratase, long-chain specific acyl-CoA dehydrogenase, 3-ketoacyl-CoA thiolase and alpha-enolase were identified as enzymes related to fatty acid oxidation [42,43], tricarboxylic acid cycle [44] and glycolysis [45]. Electron transfer flavoprotein subunit alpha and cytochrome c oxidase subunit 5A have also been related to mitochondrial respiration [46].…”
Section: Plos Onementioning
confidence: 99%
“…The other proteins included enzymes in the mitochondria that are mainly related to catabolism. Specifically, aconitate hydratase, long-chain specific acyl-CoA dehydrogenase, 3-ketoacyl-CoA thiolase and alpha-enolase were identified as enzymes related to fatty acid oxidation [42,43], tricarboxylic acid cycle [44] and glycolysis [45]. Electron transfer flavoprotein subunit alpha and cytochrome c oxidase subunit 5A have also been related to mitochondrial respiration [46].…”
Section: Plos Onementioning
confidence: 99%
“…The authors concluded that α-LA-oleic acid exerted its antitumor activity by disrupting cytoskeleton stability and cell motility, and by inhibiting DNA, lipid, and adenosine triphosphate synthesis, leading to cellular stress and activation of programmed cell death. The same authors [ 289 ] found that α-LA-oleic acid treatment of HeLa cells may induce a condition in which the ATP production exceeds the energy demand, which would lead to oxidative stress and activation of apoptosis.…”
Section: Anti-tumorigenic Activities Of α-Lactalbuminmentioning
confidence: 99%
“…Among, whey protein molecules have been shown to interact with different bioactive compounds, including retinol and fatty acids (Barbiroli et al., 2010; Collini et al., 2003), with the resulting complex exhibiting a variety of functional characteristics. For example, BAMLET (Bovine α‐La Made Lethal to Tumor cells) is a tumoricidal complex consisting of α‐La and oleic acid (OA) (Fang et al., 2018; Rammer et al., 2010). Another protein, β‐Lg, can also bind to OA to give a complex β‐Lg‐OA, which exhibited similar antitumor activity (Fang et al., 2015), and also resulted in the decline of IgG‐binding ability (Zhong et al., 2019).…”
Section: Introductionmentioning
confidence: 99%